The Effect of Variations in Babadotan Leaf Extract Concentration (Ageratum conyzoides L.) on the Physical Properties and Stability of Topical Gel Preparations as an Anti-Inflammatory - Sundari, Vivin; Sulastri, Titin; Suwitono, Marvel Reuben (Jurnal Biologi Tropis, 2025)
Abstract:  Inflammation is a body defense response to antigen exposure, infection, cell damage, allergens, irritants, and injury. The antibacterial activity of babadotan leaves can prevent inflammation due to microbial infections. This study aims to create and evaluate a topical gel preparation containing babadotan leaf extract (Ageratum conyzoides L.) as an anti-inflammatory agent. Babadotan leaf extract was obtained through a maceration method using 96% ethanol. The resulting gel preparation was then evaluated through various tests, including homogeneity, organoleptic properties, adhesiveness, spreadability, pH, and viscosity. The results of the study obtained a homogeneity test for all gel formulas were uniform. The organoleptic results of the gel had a distinctive odor of babadotan leaves, a thick, slightly sticky texture. The spreadability test found a range of 5.5-6.6 cm where the gel had good consistency. The adhesiveness test met the requirements of F1 5 seconds; F2 6 seconds; F3 9 seconds. The pH test F1 6.2; F2 6.0; F3 5.8. And the viscosity test F1 8.431 mPa·s; F2 8.604 mPa·s; F3 8.792 mPa·s, for aroma, F1 and F2 received a positive response (70–90% of panelists liked it). The conclusion is that the gel preparation containing babadotan leaf extract has good physical properties and shows stability during storage under various conditions.